Risk Management Implementation in Strengthening Good Pension Fund Governance: A Case Study at Pension Fund XYZ - Rahmawati, Nur; Iswahyudi, Catur; Susanti, Maria (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Pension funds are crucial for ensuring the financial well-being of retirees, yet they face complex risks that could threaten their sustainability. This study examines the implementation of risk management to support Good Pension Fund Governance (GPFG) at Pension Fund XYZ. Using a qualitative case study approach, including interviews, document analysis, and observation, the findings show that Pension Fund XYZ has aligned with key Financial Services Authority (OJK) regulations, such as active oversight, updated risk policies, and risk-based internal audits. However, challenges remain in information systems, setting risk limits, and human resource capacity. Management commitment, regulatory compliance, and a risk-aware culture serve as enablers, while weak information systems and insufficient control mechanisms pose significant obstacles to effective risk management. Strengthening risk management is therefore essential for achieving accountable and sustainable pension fund governance. The Health Level Assessment indicates that Pension Fund XYZ is in a Fairly Healthy condition, with sufficient capacity to withstand changes in business conditions and external factors.